KINERJA KARYAWAN PT. ANUGRAH HARISMA BARAKAH: DAMPAK LOCUS OF CONTROL, KARAKTERISTIK PEKERJAAN, DAN KOMUNIKASI KERJA - Rizki, Selvi Dilyanti (JIM : Journal Of International Management, 2024)
This study aims to analyze the effect of locus of control, job characteristics and work communication on the performance of employees of PT. Anugrah Harisma Barakah kec. South Kabaena. The population in this study were all employees of PT. Anugrah Harisma Barakah kec. South Kabaena by using the sampling method, namely the Slovin formula where there are 75 respondents as research samples in this case employees of PT. Anugrah Harisma Barakah, South Kabaena sub-district as many as 300 employees. Data collection method by distributing questionnaires to respondents.The data analysis using the SPSS Version 22 program.The results of this study indicate that locus of control, job characteristics and work communication simultaneously have a positive and significant effect on employee performance, job characteteristics have a positive and significant influence on employee performance, as well as work communication. Has a positive and significant effect on employee performance.